Transitional Objects to Faciliate Grieving Following Perinatal Loss. (October 2017) - LeDuff, Lawrence D.; Bradshaw, Wanda T.; Blake, Stephanie M.
Abstract : Background: Parents who experience a perinatal loss often leave the hospital with empty arms and no tangible mementos to validate the parenting experience. Opportunities to create parenting experiences with transitional objects exist following the infant's death. Purpose: This article offers suggestions for staff in units where infant loss is possible to best assist parents in optimal grieving through the offering of transitional bereavement objects. Methods/Search Strategy: CINAHL Complete, MEDLINE, and the Cochrane Database of Systematic Reviews were searched using the following key words—perinatal bereavement, grief, perinatal loss, transitional objects, bereavement photography—and the search was limited to 5 years and the English language. Findings/Results: Recommendations exist and are well supported by leading neonatal and perinatal nursing and medicine organizations for the use of transitional objects to facilitate healthy grieving when parents experience perinatal loss. Transitional objects are mementos that validate the meaning of parenthood—even if the physical act of parenting was brief. Nursing and medical staff have significant roles in guiding parents to a healthy state of bereavement and ultimately managing long-term grief. Implications for Practice: Transitional objects can be provided by staff that are low-cost or free, such as taking photographs for parents, or they can involve purchased products from perinatal bereavement programs. In the latter case, funding needs are a consideration for budgeting decisions. Implications for Research: Immediately following a loss, parents experience a brief sense of healing after receiving mementos of their infant. However, further research is needed to assess long-term effects of receiving transitional objects following perinatal loss.